Cobalt-Catalyzed Hydroxyperfluoroalkylation of Alkenes with Perfluoroalkyl Bromides and Atmospheric Oxygen - Sun, Qilin; Pang, Liangzhi; Mao, Shuxian; Fan, Wu; Zhou, Yuyi; Xu, Jing; Li, Suhua; Li, Qiankun (Synthesis, 2021)
A mild and efficient method for the cobalt-catalyzed hydroxyperfluoroalkylation of alkenes has been developed. This method demonstrated broad substrate scope, good yields, and mild conditions with the tolerance of mono-, di-, and trisubstituted alkenes including both styrenes and non-activated aliphatic olefins. This strategy offered a valuable solution for rapid and efficient construction of β-perfluoroalkyl alcohols using widely available and inexpensive perfluoroalkyl bromides and atmospheric oxygen.
Keywords: cobalt; hydroxyperfluoroalkylation; alkenes; perfluoroalkyl; tertiary amine